Bacteria-Induced Calcite Precipitation for Engineering and Environmental Applications - Purnima Baidya; Bhim Kumar Dahal; Archana Pandit; Dev Raj Joshi (Advances in Materials Science and Engineering)
Numerous engineering and environmental issues can be resolved using the bacterial-induced calcite precipitation (BCP), which has the potential to be environmentally friendly, sustainable, and economical. In BCP, bacterial enzymes used substrates and divalent cations to bind negatively charged ions to the bacterial surface and produce biocementation. Various metabolic pathways involved in the calcite precipitation and ureolysis are the principal bacterial pathways that have been illustrated by most bacteria including Sporosarcina pasteurii, Bacillus subtilis, and Pseudomonas putida. Ammonia is produced by these bacteria, which is toxic and should be eliminated. Therefore, BCP via carbonic anhydrase could be a preferred option because the end-products are not toxic. The growing global requirement of ground improvement boosted the demand for biostabilization because of its numerous benefits, including environmental issues. Dust suppression, remediated soil contaminants, polychlorinated biphenyl calcium ions, and CO2 sequestration, proving that BCP is environmentally friendly and sustainable. Furthermore, for fine-grained soils having pores smaller than 0.5 μm, the enzyme-induced calcite that uses enzymes instead of bacteria is more suitable to stabilize the soil by precipitating the calcite. The use of BCP as binders for soil stability and strengthening, innovative construction materials, subsurface barriers, and impermeable crusts is an emerging field. Calcite precipitated in the pores increases strength more than 20 times, resulting in a significant reduction in compressibility. Similarly, reduced soil permeability to up to 99% broadens its applicability. This review argues that BCP can be induced by multiple approaches, including urease expressing bacteria and carbonic anhydrase expressing bacteria as well as free enzymes.